Eksplorasi Hubungan Resiprokal antara Foreign Direct Investment dan Pertumbuhan Ekonomi di Negara-Negara IMT-GT - Moneyzar Usman; Arivina Ratih; Heru Wahyudi; M. Julian Tama (CV. ITTC INDONESIA, 2026)
The Indonesia–Malaysia–Thailand Growth Triangle (IMT-GT) subregional economic cooperation promotes regional economic integration through trade, investment, and regional connectivity. In this context, Foreign Direct Investment (FDI) is considered an important factor influencing economic growth through technology transfer, productivity enhancement, and production capacity expansion. However, the relationship between FDI and economic growth in IMT-GT countries remains inconclusive. This study aims to analyze the causal relationship between Foreign Direct Investment (FDI), economic growth, exports, and imports in IMT-GT member countries, namely Indonesia, Malaysia, and Thailand. This research employs a quantitative approach using secondary time series data from 1981–2024 obtained from the World Bank. The variables used include Gross Domestic Product (GDP), Foreign Direct Investment (FDI), exports, and imports. The analysis applies the Augmented Dickey-Fuller (ADF) unit root test, Levin, Lin, and Chu panel unit root test, and Granger causality test using EViews 12 software. The findings indicate that all variables are stationary at the first difference level. The causality test reveals a bidirectional relationship between GDP and FDI in Indonesia and Malaysia, while Thailand shows no significant causal relationship between the two variables. In addition, Indonesia and Malaysia exhibit one-way relationships from exports to FDI, imports to FDI, and exports to imports. In Thailand, the relationship appears relatively weak and is only indicated by the effect of exports on GDP at the 10 percent significance level. This study concludes that the relationship between FDI, economic growth, exports, and imports in IMT-GT countries is not homogeneous, but is influenced by economic characteristics, trade structures, and each country’s capacity to absorb the benefits of foreign investment. Therefore, strengthening the investment climate, trade connectivity, and productivity-oriented economic policies is essential to enhance the contribution of FDI to economic growth in the IMT-GT region.